Morphological Investigations of the Cervicothoracic Sympathetic System in the Horse (Equus ferrus caballus) in Egypt - Abumandour,Mohamed M. A (Sociedad Chilena de Anatomía, 2016)
The current study was performed on twelve healthy adult horses (E. ferrus caballus) collected from Egypt were dissected to provide anatomical descriptions of bilaterally cervicothoracic sympathetic system macroscopically. On the left side, cervicothoracic sympathetic system is represented only by the caudal cervical ganglion, which presents on lateral surface of esophagus, cranial to the level of first rib. On right side, cervicothoracic sympathetic system is represented by the caudal and middle cervical ganglion. Caudal cervical ganglion was consisted of the fusion of eighth cervical and first three thoracic nerve ganglia. Caudal directed continuation branch of left ansa subclavia gave off a pericardial branch and then gave branch for ligamentum arteriosum. There are special sympatheticparasympathetic communicating branches; on left side, there is only one branch that was present on lateral surface of esophagus, while on right side, there were four branches; two from caudal cervical ganglion and two from middle cervical ganglion. The most suitable site of ganglion blocks from both sides; needle was placed medioventrally between the articulation of first and second rib.